Pengaruh Brief Konseling Aktivitas Fisik Terhadap Tekanan Darah Penderita Hipertensi Di Kelurahan Karangayu - Helda Delia; Felicia Risca Ryandini; Suksi Riani (STIKes Ibnu Sina Ajibarang, 2023)
Hypertension is an increase in arterial blood vessels with a systolic value equal to or above 140 mmHg and a diastolic value equal to or above 90 mmHg. In Central Java Province the prevalence of hypertension reached 68.6%. Patients with hypertension can experience complaints of dizziness, headaches, neck stiffness, and dizzy eyes. Health education media in this study was in the form of a booklet. The purpose of this study was to determine the effect of brief physical activity counseling on blood pressure of hypertensive patients in the Karangayu sub-district. The research design uses quantitative research with analytical descriptive namely Quasy Experiment with one group pre test post test design. The number of samples in this study were 60 respondents with the data collection technique using purposive sampling. The results of the study using the Wilcoxon test showed that there was a significant effect on the blood pressure of hypertensive patients with hypertension in the Karangayu sub-district with a p value <0.05 (0.000) so that Ha was accepted and Ho was rejected.